Efektivitas Pelayanan Publik Sebelum Dan Selama Pandemi Covid-19 Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Aceh Selatan - Febriani Dwi Syahputri dwisyahputri; Najamudin Najamudin (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
This article aims to determine the effectiveness of public services before and during the covid-19 pandemic at the South Aceh Regency Population and Civil Registration Office, where the effectiveness of services before the pandemic was much better than the effectiveness of services during the pandemic. This research uses a qualitative method with a case study approach, how to collect data through interviews and data collection from related agencies. The results of what the researchers obtained were that the effectiveness of public services at the Population and Civil Disability Service Office was still not fully effective due to the addition of new requirements during the COVID-19 pandemic.